The how of multistakeholder engagement. - Verzosa, Cecilia Cabanero; Asian Development Bank (Manila,Philippines Asian Development Bank, [2019])
Development actors must be ready to share power to achieve effective multistakeholder engagement. This means (i) being willing to listen to voices of dissent as well as of agreement, (ii) providing space to review the design and implementation of change interventions, and (iii) replacing incentives and institutional processes that perpetuate the status quo with mechanisms that promote transparency and reduce asymmetric information. These actions will allow multistakeholder groups to articulate their needs and help shape change processes.
Keywords: Public administration; Performance standards -- Management; Strategic planning; Electronic book